LIF maintains mouse embryonic stem cells pluripotency by modulating TET1 and JMJD2 activity in a JAK2-dependent manner. (11th February 2021) - Wulansari, Noviana; Sulistio, Yanuar Alan; Darsono, Wahyu Handoko Wibowo; Kim, Chang-Hoon; Lee, Sang-Hun
Abstract: The LIF-JAK2-STAT3 pathway is the central signal transducer that maintains undifferentiated mouse embryonic stem cells (mESCs), which is achieved by the recruitment of activated STAT3 to the master pluripotency genes and activation of the gene transcriptions. It remains unclear, however, how the epigenetic status required for the master gene transcriptions is built into LIF-treated mESC cultures. In this study, Jak2, but not Stat3, in the LIF canonical pathway, establishes an open epigenetic status in the pluripotency gene promoter regions. Upon LIF activation, cytosolic JAK2 was translocalized into the nucleus of mESCs, and reduced DNA methylation (5mC levels) along with increasing DNA hydroxymethylation (5hmC) in the pluripotent gene ( Nanog / Pou5f1 ) promoter regions. In addition, the repressive histone codes H3K9m3/H3K27m3 were reduced by JAK2. Activated JAK2 directly interacted with the core epigenetic enzymes TET1 and JMJD2, modulating its activity and promotes the DNA and histone demethylation, respectively. The JAK2 effects were attained by tyrosine phosphorylation on the epigenetic enzymes. The effects of JAK2 phosphorylation on the enzymes were diverse, but all were merged to the epigenetic signatures associated with open DNA/chromatin structures. Taken together, these results reveal a previously unrecognized epigenetic regulatory role of JAK2 as an important mediator of mESC maintenance. Abstract : JAK2 is the key mediator of LIF-mediated epigenetic control in mouse embryonic stem cells pluripotency and maintenance. JAK2 activation by LIF induces its translocation to the nucleus. Activated JAK2 directly interacts with core epigenetic enzymes TET1 and JMJD2, modulating its activity and promotes the DNA and histone demethylation, respectively. JAK2 also induces DNA methyltransferases phosphorylation and primes it for degradation. All together, these JAK2-mediated effects establish an open epigenetic status in the pluripotency genes promoter regions.